2018
DOI: 10.2514/1.j056586
|View full text |Cite
|
Sign up to set email alerts
|

Flow Control of Tip/Edge Vortices

Abstract: Location, strength and structure of tip and edge vortices shed from wings and bodies can be manipulated by using flow control techniques. Flow physics of these approaches involve flow separation from the edge, roll-up into the vortex, wing flow regime, vortex instabilities, vortex-vortex interactions, and vortex-turbulence interactions. Actuators include continuous and unsteady blowing and suction, bleed, and control surfaces, which add momentum, vorticity and turbulence into the vortices. It is noted that act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Over the years, more detailed investigations have been carried out to reveal the formation, evolution and instability mechanisms of the tip vortices (McCormick, Sherrier & Tangler 1968;Crow 1970;Francis & Kennedy 1979;Katz & Galdo 1989;Green & Acosta 1991;Devenport et al 1996;Birch et al 2004;Duraisamy 2005;Giuni 2013;Edstrand et al 2016Edstrand et al , 2018a. Based on the insights from these studies, various control techniques to alleviate the tip vortices have also been developed to reduce the induced drag and wake vortex hazards (Gursul et al 2007;Greenblatt 2012;Edstrand et al 2018b;Gursul & Wang 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, more detailed investigations have been carried out to reveal the formation, evolution and instability mechanisms of the tip vortices (McCormick, Sherrier & Tangler 1968;Crow 1970;Francis & Kennedy 1979;Katz & Galdo 1989;Green & Acosta 1991;Devenport et al 1996;Birch et al 2004;Duraisamy 2005;Giuni 2013;Edstrand et al 2016Edstrand et al , 2018a. Based on the insights from these studies, various control techniques to alleviate the tip vortices have also been developed to reduce the induced drag and wake vortex hazards (Gursul et al 2007;Greenblatt 2012;Edstrand et al 2018b;Gursul & Wang 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the vibrating wire, an unsteady forcing technique using periodic jet impulses, namely the ''synthetic jet'', was employed as an effective actuators 71 in active flow control applications for delaying stall and increasing lift, [72][73][74][75][76][77][78][79] thrust enhancement, 80 and tip vortex control. 81,82 The outcomes indicated that such an unsteady forcing technique using periodic jet impulses could energize shear layer instabilities and result in reattachment over the suction surface of the wing. Hence, the local flow excitation technique of using a synthetic jet was adopted at close to the leading edge of an AR ¼ 2 flat-plate wing in order to attenuate the self-induced roll oscillations (Figure 19).…”
Section: Active Flow Control Approachesmentioning
confidence: 99%
“…However, sustaining the leading-edge vortices is desired for aerodynamic performance increase of swept wing configurations (e.g., delta wings). In [1], the authors identified three vortex types based on their applications: tip vortices, leading-edge vortices, and wake vortices, and discussed relevant vortical flow phenomena (edge separation, vortex roll-up, vortex instabilities, and vortex interactions) and corresponding control parameters (swirl angle, pressure distribution, location of disturbance injection, frequency). Control methods targeting the manipulation of each flow feature discussed were assessed in the paper mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Control methods targeting the manipulation of each flow feature discussed were assessed in the paper mentioned. Irrespective of the actuator type (fluidic, moving-surface, or plasma actuator), the control mechanism either adds or removes vorticity, momentum, or turbulence [1].…”
Section: Introductionmentioning
confidence: 99%